ARTKIT: Environmental and art center from demolished buildings case Longyearbyen - Kinnunen, Jenni (2021)
This thesis seeks to connect circular economy and history preservation and explores these themes through reflective writing and architectural design. The aim of this thesis is to produce a design with materials from demolished buildings to increase value and identity locally. The case in this thesis is Longyearbyen, the capital of Svalbard, a small town in transition in the Arctic. A major inspiration and aid for this thesis has been the LPO architects’ project Rett Plass – Rett Form, which studies architectural circular economy possibilities in Svalbard. This thesis consists of three parts. The essay part of the thesis recognizes issues in the linear building industry, and demolition, and argues for the value of the common building. It is argued that the value could be increased by realizing circular economy potentials in the built fabric. As a means to potentially increase the value of a building, history preservation via reuse is explored. Then, case studies which employ circular economy and material reuse are examined through different lenses. The second part of the thesis forms the context for the design through studying the history, climatic conditions and the people and built environment of Svalbard and Longyearbyen. Understanding of Longyearbyen and its history and community is gained from various publications. A local aspiration to become heavily gravitated towards circular economy is identified. The town is transitioning from an industrial coal company town toward a community oriented towards culture, tourism and ecological revival. An awareness of various existing plans for local areal and building development is used to guide the design proposal. The findings from the study of Svalbard and Longyearbyen are used to create the program for the design proposal. The LPO architects provided a large database of soon to be demolished buildings to examine and use in this thesis. The architectural materials, maps and photos were studied, and five buildings and a coal mining structure were chosen for closer ...